Mechanism of Change in Demographic Ageing - EL-ROUBY, M.G. (Dirasat in Economics and Business, 1981)
Of all contemporary phenomena, Demographic Ageing is, as Sauvy has put it, "the least doubted, the best measured, the most regular in its effects and the easiest to forecast well ahead as well as the most influential. Yet it is probably the least known of all" I Demographic ageing or ageing of human populations differs significantly from ageing of the individuals forming these populations both in the causes underlying the process of ageing and in the consequences occurring after the process has developed. In individuals'ageing, individuals are treated as separate units with the incidence of ageing recorded for each of them as his age increases with time. At advanced age, contribution of the individual to the luxury of his life gradually diminishes up to a stage in which the individual's basic needs can hardly be met as a result of his limited physical and intellectual abilities. Whereas in population ageing, all individuals constituting a particular population are dealt with as a one single unit, the aggregate of the individuals, with an average age computed for the whole unit at varying points of time and the changes in the structure of the aggregate and its age are recorded. The age of the population may not necessarily increase with time as it is the case with individual's ageing and therefore, the population may proceed in either directions: towards ageing or rejuvenation. Contrasted with individual's ageing, population ageing may be advantgeous to the population in various economic and social spheres.